Are the Wall Street Analyst Rankings Popularity Contests? - Emery, Douglas R.; Li, Xi (Journal of Financial and Quantitative Analysis, 2009)
Abstract We investigate the (sell-side) analyst rankings of Institutional Investor (I/I) and The Wall Street Journal (WSJ), using data from 1993–2005. We find that factors with a primary component of recognition are the most important determinants of the rankings, although performance measures are statistically significant determinants in some cases. The single exception to this finding is with existing WSJ stars, where industry-adjusted investment-recommendation performance is the only significant determinant of repeating as a star. Further, in the year after becoming stars, the recommendations of WSJ stars are significantly worse than those of nonstars; and the recommendations and earnings forecasts of I/I stars, as well as the earnings forecasts of WSJ stars, are not significantly different from those of nonstars. We conclude that these rankings are largely “popularity contests.”